FERRITINA: intervalos de referência para adultos no Estado do Rio Grande do Norte - Saldanha, Valdjane (2009)
Ferritin is a protein composed of heavy and light chains, non-covalently linked and which accommodates, in its core, thousands of atoms of iron. Furthermore, this protein represents the stock of iron in the body and it is characterized as an acute marker and predictor of diseases, such as iron deficiency anemia, hereditary hemochromatosis and others. Considering the variability of reference values and the analytical methods currently available, the aim of this work was to propose 95% confidence intervals for adults in the State of Rio Grande do Norte, Brazil, after determining the average concentration of serum ferritin for both sexes, beyond its correlation with the age. We analyzed 385 blood samples, collected by venipuncture from individuals residing in the State, after 12-14 hours of fast. The populational sample had 169 men and 216 women between 18-59 years old, which filled a questionnaire on socioeconomic, food habits and accounts about previous and current diseases. The sample collections were itinerant and the results of erythrogram, fasting glucose, alanine aminotransferase, aspartate aminotransferase, γ-glutamyl transferase, urea, creatinine, leukocyte count and platelets, beyond C-reactive protein, were issued to each participant, so that, after selection of the apparently healthy individuals, the dosage of serum ferritin was carried out. Statistical analysis was performed using the softwares SPSS 11.0 Windows version, Epi Info 3.3.2 and Graf instant pad (version 3.02), and the random population sample was single (finite population), for which the test of linear correlation and diagram of dispersion were also made. After selection of individuals and determination of serum ferritin, the most discrepant outliers were disregarded (N = 358, Men = 154/Women = 207) and the average value determined for the masculine sex individuals was 167,18 ng / dL; for the feminine sex individuals, the average value obtained was 81,55 ng / dL. Moreover, we found that 25% of men had values < 90,30 ng / dL; 50% ≤ 156,25 ng / dL and 75% ≤ 229,00 ng / dL. In the group of women, 25% had values < 38,80 ng / dL; 50% ≤ 65,00 ng / dL and 75% ≤ 119,00 ng / dL. Through the correlation coefficient (r = 0,23 with p = 0,003), it is possible to suggest the existence of positive linear correlation between age and serum ferritin for men. The correlation coefficient for women (r = 0,16 with p = 0,025) also confirms the existence of positive linear correlation between serum ferritin and age. Considering the analysis carried out and specific methods corroborating with the proposed benchmarks, we concluded that the average value found for men is higher than that found for women. Furthermore, this scenario rises with age for both sexes, and the 95% confidence intervals obtained were 74 ng/dL ≤ μ ≤ 89 ng/dL and 152ng/dL ≤ μ ≤183ng/dL for the feminine and masculine sex individuals respectively